2014
DOI: 10.1186/s13018-014-0067-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peroneal nerve injuries with simultaneous tendon transfer and nerve exploration

Abstract: BackgroundCommon peroneal nerve palsy leading to foot drop is difficult to manage and has historically been treated with extended bracing with expectant waiting for return of nerve function. Peroneal nerve exploration has traditionally been avoided except in cases of known traumatic or iatrogenic injury, with tendon transfers being performed in a delayed fashion after exhausting conservative treatment. We present a new strategy for management of foot drop with nerve exploration and concomitant tendon transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Heik Reichl et al (2013) common peroneal nerve reconstruction is indicated up to 6 months, they described excision of non-conducting neuroma and graft of deep and superfascial nerves by grafts from sural nerve which fixed by 9.0 proline sutures delayed reconstruction of CPN after 13 months from injury time with the case was followed up for 30 months and presented with strength grade 5 and regular pattern of gait with 90 degree active dorsiflexion [12]. Bryant et al (2014): managed (12) cases with peroneal nerve palsy with simultaneous tendone transfer and nerve exploration for (7) cases, with results superior function in all patients compared to dorsiflexion in 40% of cases treated with tendone transfer alone, with 57% of cases treated with both tendone transfer and nerve repair were able to return to running compared to 20% with tendone transfer alone [13]. Although in CPN palsy recover spontaneously in most cases, when irreversible damage to the nerve can occur so introduction of the concept of decision primary or primary & secondary reconstruction intraoperative should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Heik Reichl et al (2013) common peroneal nerve reconstruction is indicated up to 6 months, they described excision of non-conducting neuroma and graft of deep and superfascial nerves by grafts from sural nerve which fixed by 9.0 proline sutures delayed reconstruction of CPN after 13 months from injury time with the case was followed up for 30 months and presented with strength grade 5 and regular pattern of gait with 90 degree active dorsiflexion [12]. Bryant et al (2014): managed (12) cases with peroneal nerve palsy with simultaneous tendone transfer and nerve exploration for (7) cases, with results superior function in all patients compared to dorsiflexion in 40% of cases treated with tendone transfer alone, with 57% of cases treated with both tendone transfer and nerve repair were able to return to running compared to 20% with tendone transfer alone [13]. Although in CPN palsy recover spontaneously in most cases, when irreversible damage to the nerve can occur so introduction of the concept of decision primary or primary & secondary reconstruction intraoperative should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of inversion in these cases has profound clinical significance and eliminates as an option, arguably the best surgical treatment for foot drop, a tibialis posterior tendon transfer. 3,4,6,7 We predicted that this injury may be accounted for by the internal fascicular topographical organization of the sciatic, common peroneal, and tibial nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Over half the patients in the simultaneous group were able to return to running activities compared with only one in the isolated PTT group who was able to do so. 27…”
Section: Tendon Transfers and Arthrodesismentioning
confidence: 99%